Conceptual design analysis for a two-stage-to-orbit semi-reusable launch system for small satellites. (November 2018) - Maddock, Christie Alisa; Ricciardi, Lorenzo; West, Michael; West, Joanne; Kontis, Konstantinos; Rengarajan, Sriram; Evans, David; Milne, Andy; McIntyre, Stuart
Abstract: This paper presents the conceptual design and performance analysis of a partially reusable space launch vehicle for small payloads. The system employs a multi-stage vehicle powered by rocket engines, with a reusable first stage capable of glided or powered flight, and expendable upper stage(s) to inject 500 kg of payload into low Earth orbits. The space access vehicle is designed to be air-launched from a modified aircraft carrier. The aim of the system design is to develop a commercially viable launch system for near-term operation, thus emphasis is placed on the efficient use of high TRL technologies and on the commercial potential of the technical design. The vehicle design is analysed using a multi-disciplinary design optimisation approach to evaluate the performance, operational capabilities and design trade-offs. Results from two trade-off studies are shown, evaluating the choice wing area and thus aerodynamic characteristics, and the choice of stage masses and engines selection on the mission performance. Abstract : Conceptual design for horizontal two-stage spaceplane launch system for small payloads. Technical design driven by commercial viability. Trade-off through multi-disciplinary design optimisation of vehicle and trajectory.